Evaluation of quality of life in patients with ocular pterygium in the municipality of Palmas - Viegas, Marco Túlio Chater; Pinheiro, Sandra Maria Botelho; Viegas, Fabiana Richa Valim; Santos, Adojhones Frankcian da Silva; Diniz, Wande Gonçalves; Maia, Núbia Cristina de Freitas (Journal of Health Care, 2016)
Introduction: Pterygium is characterized by growth of fibrovascular tissue of the bulbar conjunctiva onthe cornea. It is a disease with greater frequency in individuals of tropical countries, affecting mainly menaged over 30 years. Objective: This study aimed to evaluate the quality of life of patients with different sizesof pterygium, in the city of Palmas/TO, Brazil. Materials and methods: Observational, cross-sectionalstudy with 60 patients, allocated into 03 groups (I, II, and III) of 20 patients each, which were organizedaccording to the degree of pterygium (1, 2, and 3, respectively). An epidemiological questionnaire andanother on quality of life (NEI VFQ-25) were completed, and the data was submitted to statistical analysis.Results: When comparing the visual acuity and quality of life scores among the groups, according tothe degree of pterygium, it was observed that in Group I, LogMAR (Logarithm of the Minimum Angleof Resolution) visual acuity was 0.015 (±0.067); in group II, visual acuity was 0.080 (±0.132); and ingroup III was 0.067 (±0.127), with p=0.12. Conclusion: There was a change in quality of life scores inboth groups, but without statistical significance among them, although differences have been found in thesubjective assessment of visual quality among groups. We recommend further studies with a larger numberof participants.
Keywords: Pterygium; Quality of life; Health questionnaires; Statistical analysis; Visual acuity